2008
DOI: 10.1038/nature06951
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in catechol-O-methyltransferase and 2-methoxyoestradiol is associated with pre-eclampsia

Abstract: Despite intense investigation, mechanisms that facilitate the emergence of the pre-eclampsia phenotype in women are still unknown. Placental hypoxia, hypertension, proteinuria and oedema are the principal clinical features of this disease. It is speculated that hypoxia-driven disruption of the angiogenic balance involving vascular endothelial growth factor (VEGF)/placenta-derived growth factor (PLGF) and soluble Fms-like tyrosine kinase-1 (sFLT-1, the soluble form of VEGF receptor 1) might contribute to some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
346
2
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(377 citation statements)
references
References 32 publications
22
346
2
7
Order By: Relevance
“…14 In the normal mouse placenta, we found that pimonidazole staining was highest in the spongiotrophoblast and trophoblast giant cell layers of the junctional zone, confirming previous results. 34,35 This region is primarily perfused by maternal blood in venous channels draining the labyrinthine sinusoids of the placenta. 36 This blood is depleted of nutrients and oxygen and enriched in wastes from the fetus, which may explain why this region is relatively hypoxic.…”
Section: Discussionmentioning
confidence: 99%
“…14 In the normal mouse placenta, we found that pimonidazole staining was highest in the spongiotrophoblast and trophoblast giant cell layers of the junctional zone, confirming previous results. 34,35 This region is primarily perfused by maternal blood in venous channels draining the labyrinthine sinusoids of the placenta. 36 This blood is depleted of nutrients and oxygen and enriched in wastes from the fetus, which may explain why this region is relatively hypoxic.…”
Section: Discussionmentioning
confidence: 99%
“…100 Increased receptor-mediated uterine artery constriction has been also reported in models with experimental preeclampsia. Uterine arteries from the catechol-O-methyl transferase (COMT −/− ) knockout mouse 101,102 and the TgA rat (transgenic human angiotensinogen × human renin) exhibited augmented uterine artery responsiveness to phenylephrine and angiotensin II, respectively. 9 Reactivity to agonist-induced vasodilation in the main uterine artery relies primarily on NO, although PGI 2 contribution has been reported.…”
Section: Uterine Artery Functionmentioning
confidence: 99%
“…17b-Estradiol is converted to hydroxyestradiol by the action of cytochrome P450, and hydroxyestradiol is converted to 2-methoxyestradiol by the action of catechol-O-methyltransferase (COMT). 29,30 The decrease of 2-methoxyestradiol by the deficient of COMT induced the PE-like phenotype via the decrease of 2-methoxyestradiol in mice, 29,30 indicating that some derivatives of estradiol might be implicated in the genesis of PE. Several studies of polymorphisms of estrogen receptor gene also suggested the possible implication of estrogen for the genesis of PE.…”
Section: Discussionmentioning
confidence: 99%